Publications Produced by the Francis Galton Laboratory for National Eugenics. (2nd December 2021) - Cain, Joe
Abstract: In 1907, Karl Pearson created the Francis Galton Laboratory for National Eugenics at University College, University of London. His ambitions emphasised both discipline building and the assertion of primacy for university research in eugenics over political activism. An academic entrepreneur, Pearson operated the 'Eugenics Laboratory' as a publishing house or imprint. It published five series. Because titles in each series were printed as ad hoc private separates for much of their duration, current bibliographic records show considerable variation and error while historical studies of the Eugenics Laboratory tend toward fragmentation. This paper presents a comprehensive inventory for each series associated with the Eugenics Laboratory, and it offers brief analysis of emerging patterns. The series inventoried are: (1) Eugenics Laboratory Lectures, (2) Eugenics Laboratory Memoirs, (3) The Treasury of Human Inheritance, (4) Questions of the Day and of the Fray, and (5) Studies in National Deterioration .